Improved Alignment of PEDOT:PSS Induced by in-situ Crystallization of “Green” Dimethylsulfone Molecules to Enhance the Polymer Thermoelectric Performance - Zhu, Qiang; Yildirim, Erol; Wang, Xizu; Soo, Xiang Yun Debbie; Zheng, Yun; Tan, Teck Leong; Wu, Gang; Yang, Shuo-Wang; Xu, Jianwei (Frontiers in Chemistry, 2019)
Dimethylsulfone (DMSO2), a small organic molecule, was observed to induce the alignment of poly(3,4-ethylenedioxythiophene):poly(4-styrenesulfonate) (PEDOT:PSS) via in-situ crystallization in PEDOT:PSS mixture, which was verified by field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD) and atomic force microscopy (AFM). A chemically stable dopant, DMSO2, remarkably raised the electrical conductivity of the PEDOT:PSS film, which was fabricated from pre-mixed solution of PEDOT:PSS and DMSO2, up to 1080 S/cm, and more importantly, such a PEDOT:PSS film showed a long-term humidity stability and it retained near 90% electric conductivity after 60 days, suggesting DMSO2 is promising for an eco-friendly alternative to replace dimethyl sulfoxide (DMSO), ethylene glycol (EG) and various acids dopants that have been widely employed to dope and post-treat PEDOT:PSS. Pairwise interaction energies and free energy of solvation between PEDOT:PSS and DMSO2 were calculated by first-principles and molecular mechanics, respectively, revealing the mechanism of DMSO2 in enhancing the electrical conductivity.